2010
DOI: 10.1098/rsbl.2009.0986
|View full text |Cite
|
Sign up to set email alerts
|

Diet effects on honeybee immunocompetence

Abstract: The maintenance of the immune system can be costly, and a lack of dietary protein can increase the susceptibility of organisms to disease. However, few studies have investigated the relationship between protein nutrition and immunity in insects. Here, we tested in honeybees (Apis mellifera) whether dietary protein quantity (monofloral pollen) and diet diversity (polyfloral pollen) can shape baseline immunocompetence (IC) by measuring parameters of individual immunity (haemocyte concentration, fat body content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
540
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 670 publications
(595 citation statements)
references
References 19 publications
(22 reference statements)
20
540
2
6
Order By: Relevance
“…For example, higher protein may benefit insects that need to upregulate their P450 enzymes and other detoxification pathways. In adult honeybees, Wahl and Ulm (1983) showed that the quality of pollens fed to young bees affected their subsequent response to pesticides, and Alaux et al (2010b) found effects of pollen diets on immunocompetence. The resistance of laboratoryreared larvae to fungal parasites in the genus Aspergillus is enhanced by supplementing the diet with pollen if the royal jelly component of the larval diets is reduced (Foley et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, higher protein may benefit insects that need to upregulate their P450 enzymes and other detoxification pathways. In adult honeybees, Wahl and Ulm (1983) showed that the quality of pollens fed to young bees affected their subsequent response to pesticides, and Alaux et al (2010b) found effects of pollen diets on immunocompetence. The resistance of laboratoryreared larvae to fungal parasites in the genus Aspergillus is enhanced by supplementing the diet with pollen if the royal jelly component of the larval diets is reduced (Foley et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The results of Lee et al (2006) and Povey et al (2009) indicate that dietary protein is a key nutritional component affecting immunity (see also (Alaux et al, 2010;Fellous and Lazzaro, 2010;Peck et al, 1992), and that caterpillars are able to self-medicate for infection by selecting a dietary composition that best supports immune defense (see also Singer et al, 2009). …”
Section: Nutritional Immunology: Taking a Multi-dimensional Approachmentioning
confidence: 99%
“…In order to develop sustainable solutions, the genetic mechanisms that allow honey bees to detect Varroa infested brood and remove diseased larvae Gilliam, 1998a, 1998b) or to tolerate Varroa parasitization without experiencing negative effects (Martin and Medina, 2004;Navajas et al, 2008) have been studied. Other approaches aimed at mitigating the effects of mite infestation on the bees through supplementary nutrition or other external inputs, that may compensate the detrimental effect of the mite (Alaux et al, 2010), have also yielded promising results.…”
Section: Introductionmentioning
confidence: 99%